Compliance with Pregnancy Prevention Recommendations for Isotretinoin Following the Amendment of the European Union Pregnancy Prevention Program: A Repeat Study in Estonia - Maaja Ivask; Katrin Kurvits; Maia Uusküla; Anne Juppo; Ott Laius; Mia Siven (Adis, Springer Healthcare, 2023)
Abstract Background Isotretinoin, indicated for severe acne, is a potent teratogen and therefore contraindicated in pregnancy. Thus, the pregnancy prevention program (PPP) for isotretinoin has been introduced. Objectives The aim of this study was to assess the concomitant use of isotretinoin and effective contraception and the rate of potential isotretinoin-exposed pregnancies in females of childbearing age in 2017-2020 in Estonia. In addition, we aimed to evaluate whether compliance with the PPP has improved compared with the previous study conducted in Estonia covering the period of 2012-2016. Methods This retrospective, nationwide study using prescription and healthcare claims data included 2575 females aged 15-45 years who started using isotretinoin between 2017 and 2020. Results For 64.7% of females of childbearing age, no concurrent use of an effective contraceptive was detected while using isotretinoin. A moderately higher contraceptive coverage (35.3%) was observed compared with the previous study (29.7%) (p < 0.001). Complete contraception coverage was highest in females aged 30-39 years with an adjusted OR of 12.8 (p < 0.001) compared with the age group 15-19 years and 2.47 (p < 0.001) compared with the age group 20-29 years. 17 pregnancies coincided with the isotretinoin treatment-related period. The risk for potential isotretinoin-exposed pregnancy was 6.6 (95% CI 3.9-10.5) per 1000 treated females of childbearing age over the 4-year observation period. The risk for potential isotretinoin-exposed pregnancies per 1000 treated females was 1.0 in females aged 15-19 years, 11.6 in females aged 20-29 years, 8.8 in females aged 30-39 years, and 7.4 in females aged 40-45 years (p = 0.009). Conclusion A slight improvement in complete contraceptive coverage during isotretinoin use has not resulted in a decrease in the risk of isotretinoin-exposed pregnancies. The contraceptive usage and risk for pregnancy vary greatly across age groups, suggesting the need for a more targeted approach to improve the effectiveness of the PPP.